1953
DOI: 10.1007/bf02638327
|View full text |Cite
|
Sign up to set email alerts
|

Suggested spectrophotometric methods for grading green soybean oil

Abstract: SummaryPossible spectrophotometric methods which could replace the present system of grading crude green soybean oils are given below in order of convenience. The limits are approximate values. Measurement of optical density of crude oils at 700 mμ in 21.8‐mm. tubes. Grade 2 limits would be at optical densities of 0.5 and 0.7 Measurement of refined oils at 690 mμ in 21.8‐mm. tubes. The limits for Grade 2 would be at optical densities of 0.4 and 0.6. Measurement of refined oil at 670 mμ in 8.0‐mm. tubes. Lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1954
1954
1990
1990

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…Total free fatty acid content in all the cultivare under study decreased as the beans become more mature as is reported by others also (Melvin et al, 1953; Feka et al, 1971; Urbanski et al, 1980;Yao et al, 1983). The result is expected since the free fatty acids are being utilized for oil synthesis during seed maturation (Yao et al, 1983).…”
Section: Discussionsupporting
confidence: 80%
“…Total free fatty acid content in all the cultivare under study decreased as the beans become more mature as is reported by others also (Melvin et al, 1953; Feka et al, 1971; Urbanski et al, 1980;Yao et al, 1983). The result is expected since the free fatty acids are being utilized for oil synthesis during seed maturation (Yao et al, 1983).…”
Section: Discussionsupporting
confidence: 80%
“…Milner and Geddes (1946) suggested that freeze-damaged seed coats are ruptured, and this encourages mold mycelial penetration and mold growth. Melvin et al (1953) also found that as the proportion of damaged frozen bean seeds increased, so did the free fatty acid content of the crude lipid. Milner et al (1943) reported that as the percentage of damaged seeds in a freezestored sample increased, there was a corresponding increase in non-protein nitrogen and reducing sugars.…”
Section: Resultsmentioning
confidence: 92%
“…Instead of chemical desiccation to halt maturation, Melvin et al (13) picked soybeans from the field and froze them at 0~ to obtain freeze-damaged soybeans. Urbanski et al (14) harvested green soybean pods by hand and held them at -5.5~ for six hr to impart freeze damage to the beans.…”
Section: Resultsmentioning
confidence: 99%